Item analysis on the effects of study visit programme in cultivating students’ soft skills: A case study - Rustam Mohd Rameli, Mohd; Abd Hadi Bunyamin, Muhammad; Joo Siang, Tan; Hassan, Zainudin; Mokhtar, Mahani; Ahmad, Jamilah; Jambari, Hanifah (International Journal of Engineering and Technology, 2018)
Experiential learning programme is an important platform in the process of cultivating student's self-development. The teaching approaches that apply experiential learning are widely implemented in higher education. The Faculty of Education in UTM has organised many of such experiential learning activities for students, however the effect of the programmes towards students' self-development is still under researched. Hence, it is still unable to fully identify their effects on cultivating students' soft skills through the process of organizing the programme and students' participations. Therefore, this study was conducted to identify the effects of experiential learning programme namely UNESA Study Visit Programme of the State University of Surabaya (UNESA) organized by the Faculty of Education UTM towards developing participants' soft skills. This case study involved 39 masters students currently majoring in Primary School Education at State University of Surabaya. The data were collected through a questionnaire involving 20 items which consist of 7 soft skills constructs. Item analysis using the Rasch Measurement Model shows that the most dominant effect is from the aspect of critical thinking and problem solving skills (logit = -1.335). Meanwhile, the positive effect is also reflected in the aspects of Professional Ethics and Moral (logit = -0.495), Communication Skills (logit = -0.410), Lifelong Learning and Information Management (logit = -0.058), Leadership Skills (logit = 0.080) and Team working Skills (logit = 0.435). Lastly, the effect on Entrepreneurship Skills is weaker with logit value = 1.440. The findings show that experiential learning programmes do provide positive effect to students and should be conducted more widely in education.Â